ANALYSIS OF THE STATE OF USE OF WATER RESOURCES IN UZBEKISTAN - Berdiyev Anwar Abdivalievich (PT ANTIS International Publisher, 2024)
The article coordinates water resource management, water distribution, water monitoring, support of water resource-related activities at the state level, nature protection policy, develops and implements national strategies and programs for the implementation of established tasks on sustainable use of nature, Environmental Protection, the effectiveness of the organization of the water resource use system is estimated not only by economic, but also by, ways to organize a system of use by indicators of environmental and social efficiency of the use of water resources are indicated